The Relationship Between Students’ Perceptions of the Role of Peers, Teaching Styles and Learning Motivation on Natural Science Learning Outcomes in Secondary School - Hariyanti, Dini; Sartika, Septi Budi (ScienceEdu, 2025)
This study was conducted with the aim of knowing and analyzing the relationship between students' perceptions regarding the role of peers, teacher teaching style, and learning motivation towards students' science learning outcomes using the correlation method. Data collection was carried out by distributing questionnaires as a research instrument. This study is a quantitative study using path analysis. The data analysis technique in this study was carried out with the help of the Smart PLS version 4.0 application. The population in this study were 180 students in 8 grade at one of the State Secondary Schools in Pasuruan City, with a random sampling technique, so that a sample of 124 students was obtained. Based on the analysis of the findings, it shows that students' perceptions of the role of peers do not have a significant effect on learning outcomes, while students' perceptions of teacher teaching styles and learning motivation have a significant effect on learning outcomes. The results of this study provide important implications in the world of education, especially related to factors that influence student learning outcomes. Further research is expected to identify other factors that can also influence student learning outcomes